Triple Layer Antireflection Design Concept for the Front Side of c-Si Heterojunction Solar Cell Based on the Antireflective Effect of nc-3C-SiC:H Emitter Layer - Erick Omondi Ateto; Makoto Konagai; Shinsuke Miyajima (International Journal of Photoenergy)
We investigated the antireflective (AR) effect of hydrogenated nanocrystalline cubic silicon carbide (nc-3C-SiC:H) emitter and its application in the triple layer AR design for the front side of silicon heterojunction (SHJ) solar cell. We found that the nc-3C-SiC:H emitter can serve both as an emitter and antireflective coating for SHJ solar cell, which enables us to realize the triple AR design by adding one additional dielectric layer to normally used SHJ structure with a transparent conductive oxide (TCO) and an emitter layer. The optimized SHJ structure with the triple layer AR coating (LiF/ITO/nc-3C-SiC:H) exhibit a short circuit current density (Jsc) of 38.65 mA/cm2 and lower reflectivity of about 3.42% at wavelength range of 300 nm–1000 nm.